4G to 6G: disruptions and drivers for optical access [Invited] - Ranaweera, Chathurika; Kua, Jonathan; Dias, Imali; Wong, Elaine; Lim, Christina; Nirmalathas, Ampalavanapillai (Journal of optical communications and networking, 2022)
The exponential growth of diverse smart mobile applications such as smart monitoring, holograms, and autonomous vehicles are driving mobile technologies toward a more intelligent and software-defined communication system. This growing demand has led to the next giant leap in next-generation wireless communication technology, i.e., sixth-generation (6G) mobile technology, which anticipates providing 1 Tbps data rates and ultralow latency over ubiquitous 3D coverage areas. However, the transport network, which connects hundreds of thousands of cell sites and the network core to enable intelligence, virtualization, and other key features of 6G, has not advanced enough to cater the dense cell deployment expected in future 6G networks. Because many aspects of 6G remain undefined, this provides us with the opportunity to take optical transport networks into design consideration to realize the benefits that 6G has to offer. To this end, in this paper, we present a comprehensive view on the role of optical access networks in supporting fourth-generation (4G), fifth-generation (5G), and beyond wireless technologies. In particular, we discuss design and deployment strategies and their challenges when using optical access as a transport solution during the evolution of wireless access technologies. For this purpose, we first identify how an optical access network is used to support high-capacity transport networks in 4G, followed by the challenges that 5G brought into optical transport networks and its diverse solutions. We conclude the paper by providing insights into how an optical transport network can be designed to support 6G.